2017
DOI: 10.1007/s13534-017-0015-6
|View full text |Cite
|
Sign up to set email alerts
|

Statistical non-parametric mapping in sensor space

Abstract: Establishing the significance of observed effects is a preliminary requirement for any meaningful interpretation of clinical and experimental Electroencephalography or Magnetoencephalography (MEG) data. We propose a method to evaluate significance on the level of sensors whilst retaining full temporal or spectral resolution. Input data are multiple realizations of sensor data. In this context, multiple realizations may be the individual epochs obtained in an evoked-response experiment, or group study data, pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…In contrast to the tERL, the dERL does not show modulation in the time range of the post-Nt. To verify time ranges of significant ERMF modulation underlying the tERL and dERL, one-way topographic analyses of variance (TANOVA) 24,25 with the factor-levels target or distractor in left versus right VF were computed for each time sample between 0 and 500 ms after stimulus onset (see "Methods" for details). The result is shown by the dashed traces below the magnetic waveforms, where significant time ranges are shown as grayed areas.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the tERL, the dERL does not show modulation in the time range of the post-Nt. To verify time ranges of significant ERMF modulation underlying the tERL and dERL, one-way topographic analyses of variance (TANOVA) 24,25 with the factor-levels target or distractor in left versus right VF were computed for each time sample between 0 and 500 ms after stimulus onset (see "Methods" for details). The result is shown by the dashed traces below the magnetic waveforms, where significant time ranges are shown as grayed areas.…”
Section: Resultsmentioning
confidence: 99%
“…3The initial activity in higher-level ventral extrastriate areas is more dorsal for the Nt and more ventral and anterior for the Pd. To validate the topographical differences between the Nt and the Pd a statistical non-parametric mapping (SnPM 25 , see "Methods" for details) analysis with the factors VF (left/right) and component (Nt, Pd) was performed for both the normalized ERMFs and the CDRs (MNLS). Figure 6b shows the VF (left/right) × component (Nt/Pd) interaction, which yields cortical regions where the distribution of the Nt and Pd differ significantly.…”
Section: Resultsmentioning
confidence: 99%
“…The data were tested in the time range of 0 to 300ms after stimulus onset, the width of the sliding window was 11.8ms (i.e., three time samples). To correct for multiple comparisons, we followed the logic of Wagner et al (2017) taking into account the original sampling frequency (fs, here 254.31Hz) and the applied low-pass filter (fc, here 50Hz). The corrected alpha level was 1-(1-0.05) 2fc/fs ≈ 0.02.…”
Section: Statistical Validation Of Amplitude Differencesmentioning
confidence: 99%
“…On the other hand, establishing the significance of observed effects is of importance for the interpretation of EEG or MEG data. In the article entitled ''Statistical Non-Parametric Mapping in Sensor Space'' [2], the authors applied statistical non-parametric mapping (SnPN), which is a nonparametric permutation test that does not need any assumption on the distribution properties of the data, to MEG sensor data. They showed that SnPN could effectively identify sensors of significantly different activity between stimulus types.…”
mentioning
confidence: 99%
“…They showed that SnPN could effectively identify sensors of significantly different activity between stimulus types. It is expected that both articles [1,2] from the same research group would significantly contribute to improving the reliability and accuracy of MEG analyses.…”
mentioning
confidence: 99%